ANALISIS PENEGAKAN HUKUM PEMILU DAN PEMILIHAN (Study Penanganan Pelanggaran di Bawaslu Kabupaten Indramayu) - Carto, Carto; Murya, Adnan; Nurmantoro, Muh. Aripin (Universitas Wiralodra, 2022)
This research/writing was made to analyze the Law Enforcement of the 2019 and 2020 Elections in Indramayu Regency, namely in the law enforcement of election/election crimes by the Gakkumdu Center based on the theory of the legal system, namely: legal structure, legal substance, and legal culture. Law Enforcement is not only related to substance but also in the process of handling it, weaknesses in the law enforcement process which later become the formulation in effective Law Enforcement of Election Crimes and Elections 2024. In this study, the author uses the normative juridical method by analyzing data through the study of library materials or secondary data which includes primary legal materials, secondary legal materials and tertiary legal materials, both in the form of documents and applicable laws and regulations relating to normative juridical analysis of enforcement. electoral and electoral law.